Assessing the impact of agricultural pressures on N and P loads and eutrophication risk. (January 2015) - Dupas, Rémi; Delmas, Magalie; Dorioz, Jean-Marcel; Garnier, Josette; Moatar, Florentina; Gascuel-Odoux, Chantal
Highlights: An assessment framework to link agricultural N/P pressures and ecological impact. Nutrient mass-balance models to estimate N/P loads in rivers at a regional scale. A set of indicators to assess eutrophication risk in freshwaters. Abstract: Excessive nutrient delivery into freshwater bodies results in increased eutrophication risk worldwide. Because high-frequency monitoring cannot be generalised to all rivers, methods are needed to assess eutrophication risk in contexts with scarce data. To this end, we present an assessment framework which includes: (i) a mass-balance model to estimate diffuse N and P transfer/retention in unmonitored catchments and (ii) a set of indicators based on N:P:Si molar ratios to assess the risk of eutrophication in freshwaters. The model, called Nutting, integrates variables that describe both agricultural pressures and physical attributes of catchments (climate, topography, soil). Nutting refines previous mass-balance models by describing nutrient pressures with soil N surplus and soil P content instead of N and P inputs, and by considering physical attributes not only as lumped variables over the entire area but also within river corridors. The model was calibrated on a set of 160 independent catchments across France and applied to all headwater catchments. We found that apparent N and P retention represented 53 ± 24% and 95 ± 29% of soil N and P surplus, respectively, and was mainly controlled by the climate and a hydrology-related connectivity index. The spatial organisation of the landscape was of secondary importance compared to the refined description of agricultural pressures. Estimated eutrophication risk was highly sensitive to assumptions about P bioavailability, hence the potential range of headwaters at risk of eutrophication spanned 26–63% of the catchments, depending on assumptions. This framework provides a generic method to assess the relative contribution of agriculture to nutrient loads and the subsequent risk of eutrophication.